Penerapan (Re)kontruksi Akuntansi Keuangan Bagi Hasil Sistem Mato Pada RMP Terang Bulan - Sartika, Dewi; Mulyani, Fitrah; Ilyas, Andre (CV. ITTC INDONESIA, 2024)
This research aims to apply (re)construction of the Mato System Profit Sharing Financial Accounting (AKBHSM) at Padang Restaurant (RMP) Terang Bulan and to determine the obstacles faced in implementing (re)construction of AKBHSM at RMP Terang Bulan. In this research the author will apply the research results of Hanif (2017) which produces a new concept in the form of AKBHSM Reconstruction which is the result of the synergy of the binary opposition of